Dramatic grain refinement and magnetic softening induced by Ni addition in FeB based nanocrystalline soft magnetic alloys. (May 2020) - Li, Z.; Parsons, R.; Zang, B.; Kishimoto, H.; Shoji, T.; Kato, A.; Karel, J.; Suzuki, K.
Abstract: The effects of Ni addition on the grain size ( D ) and coercivity ( H c ) were investigated for nanocrystalline (Fe1- x Ni x )86 B14 ( x  = 0–0.3) alloys prepared by ultra-rapid annealing of melt-spun amorphous precursors. Ni addition resulted in a structural change of the nanocrystallites from bcc to fcc and an exceptionally small D of 4.2 nm was obtained at x  = 0.3. H c was reduced dramatically from 6.8 A/m at x  = 0 to as small as 2.6 A/m at x  = 0.1. This significant improvement of magnetic softness is well understood by the effect of Ni on the local magnetocrystalline anisotropy. Graphical abstract: Image, graphical abstract